Social Stress and the Polymorphic Region of the Serotonin Reuptake Transporter Gene Modify Oestradiol‐Induced Changes on Central Monoamine Concentrations in Female Rhesus Monkeys. (21st March 2013) - Asher, J.; Michopoulos, V.; Reding, K. M.; Wilson, M. E.; Toufexis, D.
<x xml:space="preserve">Abstract</x> Psychosocial stress exposure is linked to the disruption of emotional regulation that can manifest as anxiety and depression. Women are more likely to suffer from such psychopathologies than men, indicating that sex‐based differences in gonadal steroids may be a key factor in the aetiology of stress‐induced adverse health outcomes. Oestradiol (E2) positively influences mood and cognition in females, an effect likely related to the ability of E2 to modulate the serotonin and dopamine neurotransmitter systems. Furthermore, genetic variation as a result of the polymorphism in the promoter region of the gene (SLC6A4) encoding the serotonin transporter (5HTTLPR) also can influence the ability of E2 to modulate behaviour and physiology. However, it remains uncertain whether exposure to social stress interacts with the 5HTTLPR to influence E2‐induced changes in behaviour and physiology. The present study used ovariectomised adult female rhesus monkeys to investigate acute and chronic effects of E2 on central monoamine metabolite concentrations using cerobrospinal fluid sampling. We further assessed how E2‐induced changes in monoamine metabolite levels are modified by the unpredictable stress of social subordination and the 5HTTLPR polymorphism. Levels of the serotonin metabolite 5‐hydroxyindoleacetic acid decreased significantly during chronic E2 treatment only in dominant females with the long promoter length of SLC6A4. Chronic administration of E2 decreased levels of the dopamine metabolite dihydrophenylacetic acid in a manner independent of the social status, 5HTTLPR genotype, or their interactions. Overall levels of dopamine and serotonin metabolites were increased in subordinate females, although this effect of social stress was not influenced by 5HTTLPR genotype. Together, these data emphasise how E2 can modulate central neurotransmitter systems and indicate that social subordination in female monkeys is a valid model for examining how chronic psychosocial stress alters sensitivity to E2. Future studies are necessary to elaborate how changes in central neurotransmitter metabolism affect behaviour and physiology as a result of E2 and prolonged exposure to stress.